2018
DOI: 10.1002/anie.201803766
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Nucleation and Controlled Growth for Size Predicable Synthesis of Nanoscale Metal–Organic Frameworks (MOFs): A General and Scalable Approach

Abstract: Nanoscale metal-organic frameworks (nanoMOFs) are promising porous nanomaterials for diverse applications, such as catalysis, imaging, functional membranes, and drug delivery. At the nanoscale, the size of materials is critical for their properties and utility. Herein, a straightforward and convenient strategy is developed for size precisely controlled synthesis of nanoMOFs. Unlike other approaches, this strategy can directly give nanoMOFs of predicable sizes within a wide range without the time consuming tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
120
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(125 citation statements)
references
References 37 publications
5
120
0
Order By: Relevance
“…For this purpose, ZIF‐90 was first synthesized by a controlled nucleation and growth method that was developed in our group 27. Photosensitizer MB, which may disrupt mitochondrial redox homeostasis and cause mitochondrial dysfunction by producing highly oxidative 1 O 2 under light illumination, was encapsulated into ZIF‐90 (Scheme 1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, ZIF‐90 was first synthesized by a controlled nucleation and growth method that was developed in our group 27. Photosensitizer MB, which may disrupt mitochondrial redox homeostasis and cause mitochondrial dysfunction by producing highly oxidative 1 O 2 under light illumination, was encapsulated into ZIF‐90 (Scheme 1A).…”
Section: Resultsmentioning
confidence: 99%
“…ZIF‐90 was synthesized through a controlled nucleation and growth mechanism according to published literature in our group 27. Briefly, Zn(OAC) 2 DMF solution (50 mL, 10 m m ) and 2‐ICA DMF solution (50 mL, 20 m m ) were simultaneously added to an initial 2‐ICA DMF solution (50 mL, 20 m m ) with dropping speed of 30 mL h −1 at 30 °C.…”
Section: Methodsmentioning
confidence: 99%
“…In this case, following LaMer's model, [36] ah igher solubility of the CYDC linker would drive the system to af aster supersaturation and hence to overcoming the activation energy for the nucleationb urst sooner than in the case of BTC. Thus, amixture containing CYDC as linker would initially yield more nuclei leading to smaller DEMOFc rystallites as a result.R ecent examples have shown that by controlling the supersaturation of Cu 2 + and BTC one can, indeed, fine-tune the crystallite size [37] or the film thickness. [38] Small-angle X-ray scattering to probe the pore structure with increasing defect linker concentration…”
Section: Resultsmentioning
confidence: 99%
“…The Ce‐BTC MOFs, prepared via a flowing process (Figure S1, Supporting Information), showed a rod‐like morphology with a diameter of ≈40 nm and a length in the range of hundreds of nanometers ( Figure a). X‐ray diffraction (XRD) confirmed the formation of Ce‐BTC MOFs (Figure b) .…”
Section: Methodsmentioning
confidence: 99%